2015
DOI: 10.3897/bdj.3.e6482
|View full text |Cite
|
Sign up to set email alerts
|

World Checklist of Opiliones species (Arachnida). Part 2: Laniatores – Samooidea, Zalmoxoidea and Grassatores incertae sedis

Abstract: Including more than 6500 species, Opiliones is the third most diverse order of Arachnida, after the megadiverse Acari and Araneae. This database is part 2 of 12 of a project containing an intended worldwide checklist of species and subspecies of Opiliones, and it includes the members of the suborder Laniatores, infraorder Grassatores of the superfamilies Samooidea and Zalmoxoidea plus the genera currently not allocated to any family (i.e. Grassatores incertae sedis). In this Part 2, a total of 556 species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Included genera. Fudeci González-Sponga, 1998, Kimula Goodnight and Goodnight, 1942, Metakimula Avram, 1973, Minuella Roewer, 1949, Tegipiolus Roewer, 1949 and Relictopiolus Pérez-González, Monte and Bichuette, gen. nov. (See previous family composition in [ 61 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included genera. Fudeci González-Sponga, 1998, Kimula Goodnight and Goodnight, 1942, Metakimula Avram, 1973, Minuella Roewer, 1949, Tegipiolus Roewer, 1949 and Relictopiolus Pérez-González, Monte and Bichuette, gen. nov. (See previous family composition in [ 61 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The genus Acanthominua is currently considered a member of Kimulidae [ 61 ] but the examination of two males syntypes of the type species Acanthominua tricarinata Sørensen, 1932 (repository ZMUC) revealed that the exomorphology ( Fig 19A–19C ) does not match with the familial characteristics as defined by Pérez-González and Kury [ 72 ]; therefore, Acanthominua is herein transferred to Zalmoxidae Sørensen, 1886, new family allocation . Moreover, the morphology of one male syntype of A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Part 2: LaniatoresSamooidea, Zalmoxoidea and Grassatores incertae sedis " (Kury et al 2015). Herein, reasoning for taxonomic decisions is given associated with nomenclatural acts to clarify new taxonomic changes in ​ the list presented in that work.…”
Section: Introductionmentioning
confidence: 99%